Empirical Test of Content Validity and Construct Validity of Mathematical Self-Efficacy Scale - Setiadi, Iwan (Tarbiyah : Jurnal Ilmiah Kependidikan, 2021)
The purpose of the study is to examine the instrument content validity and it’s construct validity of the mathematics self-efficacy scale based on valid dimensions. This research is part of the research on the effect of the number of scale categories on the accuracy of the prediction validity of the mathematics self-efficacy scale. The research instrument is a Likert scale questionnaire with five answer categories. Analysis of content validity using coefficient V by Aiken while construct validity uses the Confirmatory Factor Analysis method with the help of the LISREL 8.72 program. The results showed that (1) 28 of 40 items of the instrument content validity is valid in three dimensions : level, strength, and generality. (2) While 22 items out of 28 items of the instrument construct validity is proven valid as well. In conclusion, the mathematics self-efficacy scale instrument has been empirically tested valid  for its content and construct validity.